Policy brief on sustainable Small-Scale Fisheries: unlocking socio-economic benefits - AU-IBAR (AU-IBAR, 2025)
This policy brief identifies systemic barriers limiting the socio-economic potential of SSF, including: Outdated or poorly enforced policies and legal frameworks; Limited political will and inconsistent institutional support; Weak or fragmented organizational structures; Low awareness of the benefits of collective action; Poor competitiveness and market integration; Insufficient socio-economic and sectoral data to inform decision-making
Keywords: Small-scale fisheries; Poor competitiveness; Market integration; Aquaculture